Identification of RpoS (ς(S))-Regulated Genes in Salmonella enterica Serovar Typhimurium - Ibanez-Ruiz, Magdalena (American Society for Microbiology, 2000)
The rpoS gene encodes the alternative sigma factor ς(S) (RpoS) and is required for survival of bacteria under starvation and stress conditions. It is also essential for Salmonella virulence in mice. Most work on the RpoS regulon has been in the closely related enterobacterial species Escherichia coli. To characterize the RpoS regulon in Salmonella, we isolated 38 unique RpoS-activated lacZ gene fusions from a bank of Salmonella enterica serovar Typhimurium mutants harboring random Tn5B21 mutations. Dependence on RpoS varied from 3-fold to over 95-fold, and all gene fusions isolated were regulated by growth phase. The identities of 21 RpoS-dependent fusions were determined by DNA sequence analysis. Seven of the fusions mapped to DNA regions in Salmonella serovar Typhimurium that do not match any known E. coli sequence, suggesting that the composition of the RpoS regulon differs markedly in the two species. The other 14 fusions mapped to 13 DNA regions very similar to E. coli sequences. None of the insertion mutations in DNA regions common to both species appeared to affect Salmonella virulence in BALB/c mice. Of these, only three (otsA, katE, and poxB) are located in known members of the RpoS regulon. Ten insertions mapped in nine open reading frames of unknown function (yciF, yehY, yhjY, yncC, yjgB, yahO, ygaU, ycgB, and yeaG) appear to be novel members of the RpoS regulon. One insertion, that in mutant C52::H87, was in the noncoding region upstream from ogt, encoding a O(6)-methylguanine DNA methyltransferase involved in repairing alkylation damage in DNA. The ogt coding sequence is very similar to the E. coli homolog, but the ogt 5′ flanking regions were found to be markedly different in the two species, suggesting genetic rearrangements. Using primer extension assays, a specific ogt mRNA start site was detected in RNAs of the Salmonella serovar Typhimurium wild-type strains C52 and SL1344 but not in RNAs of the mutant strains C52K (rpoS), SL1344K (rpoS), and C52::H87. In mutant C52::H87, Tn5B21 is inserted at the ogt mRNA start site, with lacZ presumably transcribed from the identified RpoS-regulated promoter. These results indicate that ogt gene expression in Salmonella is regulated by RpoS in stationary phase of growth in rich medium, a finding that suggests a novel role for RpoS in DNA repair functions.